Arginine Vasopressin Injected into the Dorsal Motor Nucleus of the Vagus Inhibits Gastric Motility in Rats - Jianping Zhu; Lanlan Chang; Jinlu Xie; Hongbin Ai (Gastroenterology Research and Practice)
Background. Until now, the effect of arginine vasopressin (AVP) in the DMV on gastric motility and the possible modulating pathway between the DMV and the gastrointestinal system remain poorly understood. Objectives. We aimed to explore the role of AVP in the DMV in regulating gastric motility and the possible central and peripheral pathways. Material and Methods. Firstly, we microinjected different doses of AVP into the DMV and investigated its effects on gastric motility in rats. Then, the possible central and peripheral pathways that regulate gastric motility were also discussed by microinjecting SR49059 (a specific AVP receptor antagonist) into the DMV and intravenous injection of hexamethonium (a specific neuronal nicotinic cholinergic receptor antagonist) before AVP microinjection. Results. Following microinjection of AVP (180 pmol and 18 pmol) into the DMV, the gastric motility (including total amplitude, total duration, and motility index of gastric contraction) was significantly inhibited (P<0.05). Moreover, the inhibitory effect of AVP (180 pmol) on gastric motility could be blocked completely by both SR49059 (320 pmol) and hexamethonium (8 μmol). Conclusions. It is concluded that AVP inhibits the gastric motility by acting on the specific AVP receptor in the DMV, with the potential involvement of the parasympathetic preganglionic cholinergic fibers.